Tuasan Bentuk Kearifan Lokal Nelayan Tradisional Untuk Peningkatan Hasil Tangkapan Juga Pelestarian Biota Laut - Zulkifli Zulkifli; Renita Manurung; Agustrisno Agustrisno (Pelita Masyarakat, 2022)
This public service aims to turn lokal wisdom into a guide, an attitude and behaviour in interacting with nature, as well as transforming lokal wisdom to efforts in sustaining marine life and increasing the catch of traditional fishermen. The steps to achieve these objectives are as follows: (a) conducting socialization of the Tuasan ((Fish Aggregating Device/FAD) as lokal wisdom and the medium of marine life preservation, through short videos screening, (b), holding a training on how to create FAD with the stakeholders of Bagan Kuala Village as facilitators. The output is an increase in the knowledge of traditional fishermen about lokal wisdom related to the fishing process. In addition, several FADs were handed over to the lokal fishermen of Bagan Kuala Village for communal use.Tuasan has become a guidance in the fishing process by some traditional fishermen for such a long time. Its materials consist of coconut fronds, bamboo, sand and rope; this lokal FAD is placed at the seabed as a playground and breeding location for fishes. In addition, tuasan is also used to mark the boundaries of fishing areas. Finally, tuasan as lokal wisdom of traditional fishermen needs to be preserved because it can increase the fish catching volume while it helps the preservation process of marine life